2020
DOI: 10.1111/jcpt.13335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous administration of lidocaine on the ED50 of propofol induction dose during gastroscopy in adult patients: A randomized, controlled study

Abstract: What is known and Objective: Propofol provides a prominent sedation effect in gastroscopy. However, sedation with propofol alone during gastroscopy might result in circulatory and respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(36 reference statements)
0
13
0
1
Order By: Relevance
“…lidocaine during gastroscopy in adult patients. 30 The total dosage of propofol was unavailable in that study. 30 Pooled results demonstrated a lower propofol dosage during GEPs in the lidocaine group compared with that in the placebo group (SMD¼À0.41, 95% CI: À0.67 to À0.14, P¼0.003; I 2 ¼83%) (Fig.…”
Section: Impact Of Lidocaine On Propofol Dosage Requirementmentioning
confidence: 95%
See 1 more Smart Citation
“…lidocaine during gastroscopy in adult patients. 30 The total dosage of propofol was unavailable in that study. 30 Pooled results demonstrated a lower propofol dosage during GEPs in the lidocaine group compared with that in the placebo group (SMD¼À0.41, 95% CI: À0.67 to À0.14, P¼0.003; I 2 ¼83%) (Fig.…”
Section: Impact Of Lidocaine On Propofol Dosage Requirementmentioning
confidence: 95%
“…22,27,32e34 Focusing on the administration strategy of i.v. lidocaine, two studies 25,30 used an i.v. bolus of 1.5 mg kg À1 without subsequent infusion, while the same bolus dosage was adopted followed by a continuous lidocaine infusion at a dose of 4 mg kg À1 h À1 in two trials 21,26 and 2 mg kg À1 h À1 in three trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the effect of intravenous lidocaine on the ED 50 of propofol's induction dose for gastroscopy is still unknown. Although Liu 19 et al already found that intravenous lidocaine decreased propofol's ED 50 from 2.01mg/kg to 1.69mg/kg. In this study, sufentanil was given in addition to lidocaine.…”
mentioning
confidence: 89%
“…In recent years, intravenous lidocaine has been widely used as a perioperative analgesic agent 16 , especially in the management of acute pain in Scottish hospitals 30 . According to previous reports [31][32][33] , the dosage of intravenous lidocaine injection in this study was selected as 1.5mg/kg, resulting in signi cant propofol-sparing effect.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation